Mechanistic toxicology : - Boelsterli, Urs A. (Taylor & Francis, 2002)
Boelsterli (University of Basel) describes the general principles that link xenobiotic-induced toxicity with the molecular pathways underlying the toxic effects. Topics addressed in the textbook include bioactivation of xenobiotics to reactive metabolites, xenobiotic-induced oxidative stress, and the mechanisms of necrotic and apoptotic cell death.